2016
DOI: 10.1021/acs.energyfuels.6b02248
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Trace Elements in Coals from the Yueliangtian Mine, Western Guizhou, China: Abundances, Modes of Occurrence, and Potential Industrial Utilization

Abstract: This paper reports the geochemical compositions of coals and non-coal samples from a complete seam section in the Late Permian Longtan Formation from the Yueliangtian mine, western Guizhou, southwestern China. The abundances, modes of occurrence, and origin of elements and minerals in the Yueliangtian coal were investigated using optical microscopy, scanning electron microscopy with an energy dispersive X-ray spectrometer, X-ray powder diffraction, X-ray fluorescence spectrometry, and inductively coupled plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…The majority of the coal and non-coal rocks in the Dongdong mine fall within the trachyandesite and trachyte fields, pointing to a felsic-intermediate sediment provenance, while those in the Jinhuashan coal mine are distributed in slightly broader areas, falling within the fields of trachyandesite, trachyte, as well as rhyodacite/dacite (Figure 8B), pointing to a felsic-dominated sediment provenance. Overall, the sediment provenance of the terrigenous materials in the Weibei coalfield was characterized by felsic to intermediate chemical composition.Energies 2020, 13, x FOR PEER REVIEW 12 of 28[16,22,49,50]. The majority of the coal and non-coal rocks in the Dongdong mine fall within the trachyandesite and trachyte fields, pointing to a felsic-intermediate sediment provenance, while those in the Jinhuashan coal mine are distributed in slightly broader areas, falling within the fields of trachyandesite, trachyte, as well as rhyodacite/dacite (Figure 8B), pointing to a felsic-dominated sediment provenance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the coal and non-coal rocks in the Dongdong mine fall within the trachyandesite and trachyte fields, pointing to a felsic-intermediate sediment provenance, while those in the Jinhuashan coal mine are distributed in slightly broader areas, falling within the fields of trachyandesite, trachyte, as well as rhyodacite/dacite (Figure 8B), pointing to a felsic-dominated sediment provenance. Overall, the sediment provenance of the terrigenous materials in the Weibei coalfield was characterized by felsic to intermediate chemical composition.Energies 2020, 13, x FOR PEER REVIEW 12 of 28[16,22,49,50]. The majority of the coal and non-coal rocks in the Dongdong mine fall within the trachyandesite and trachyte fields, pointing to a felsic-intermediate sediment provenance, while those in the Jinhuashan coal mine are distributed in slightly broader areas, falling within the fields of trachyandesite, trachyte, as well as rhyodacite/dacite (Figure 8B), pointing to a felsic-dominated sediment provenance.…”
mentioning
confidence: 99%
“…(B) Diagram showing Zr/TiO 2 vs. Nb/Y ratios using the magma source discrimination diagram ofWinchester and Floyd (1977) [48].The elevated Ta, Nb, Zr, Li, and Win the Weibei coals exhibit high correlations and similar vertical distributions with HTA yields, Al 2 O 3 and SiO 2 contents (Figures 9 and 10), which represent an obvious aluminosilicate affinity and imply the terrigenous origin of these elevated elements. The Zr/TiO 2 -Nb/Y plot was widely used as an auxiliary indicator to discriminate the provenance, classification and evolution of altered volcanic ashes and associated coal bearing sequences[16,22,49,50]. The majority of the coal and non-coal rocks in the Dongdong mine fall within the trachyandesite and trachyte fields, pointing to a felsic-intermediate sediment provenance, while those in the Jinhuashan coal mine are distributed in slightly broader areas, falling within the fields of trachyandesite, trachyte, as well as rhyodacite/dacite (Figure 8B), pointing to a felsic-dominated sediment provenance.…”
mentioning
confidence: 99%
“…Pyrite is a common mineral in the Lopingian coal seams in southwestern China [8,39,[42][43][44]. From the K1 to K10 coal LTA residues, the proportion of pyrite increases gradually, from 2.7% (K3-1) to 20.4% (K10-5) and with an average of 10.5%.…”
Section: Pyritementioning
confidence: 99%
“…Chamosite is not usually observed in the coal, however, it does commonly occur in the Lopingian coals in southwestern China [39,40,42,45,49]. Two origins of chamosite have been proposed, which is either derived from the alteration of kaolinite by the injection of Fe-Mg-rich fluids during diagenesis process [40], or directly precipitated from hydrothermal fluids enriched Fe [49].…”
Section: Injection Of Low-temperature Hydrothermal Fluidsmentioning
confidence: 99%
“…Most of it was adsorbed on minerals, and the rest was in solution or substituted in minerals structures. According to recent reports, most of the fluorine in coal was adsorbed [24,27,28,37,42,43]. Studies on Songzao coal from Chongqing found that F, together with Ga, Sn, U, Th, Zr, Hf, and Ta, had positive correlations with Al 2 O 3 , suggesting that fluorine occurred in clay minerals (kaolinite and others) [19,61].…”
Section: Modes Of Fluorine Occurrence In Coalmentioning
confidence: 99%